RENAL TUBULER ASİDOZA BAĞLI AĞIR HİPOPOTASEMİ VE SOLUNUM ARRESTİ İLE ORTAYA ÇIKAN BİR PRİMER SJÖGREN SENDROMU OLGUSU - BAVUNOĞLU TÜFEKÇİ, Işıl and TUNÇKALE, Aydın and YİRMİBEŞÇİK, Sibel and; A, Ebru and; ER, Yesari and; RK, Esin and; soy, Gülen (Cerrahpaşa Medical Journal, 2014)
Background.- Sjögren’s syndrome (SS) is an autoimmune exocrinopathy that involves both glandular and extraglandular systems. This disease may cause hypokalemic quadriparalysis due to distal renal tubuler acidosis (RTA). Observation.- We report here a 19-year-old girl who presented with life-threatening hypokalemic paralysis requiring admission to an intensive care unit. Biochemical investigations showed severe hypokalemia with hyperchloremic metabolic acidosis, a spot urine pH of 6.8, and a positive urinary anion gap, establishing the diagnosis of renal tubular acidosis. A positive Schirmer's test and characteristic findings in a minor salivary gland biopsy revealed Sjogren’s syndrome as the underlying cause. She recovered following potassium and alkali replacement. Hypokalemic quadriparalysis due to distal renal tubuler acidosis (RTA) has not previously been reported in Turkish literature.